Factors affecting spatio-temporal occurrence of sympatric civets in Parsa-Koshi Complex, Nepal. - Bishal Subedi; Sandeep Regmi; Amrit Nepali; Niraj Regmi; Amir Basnet; Krishna Tamang; Bishnu Aryal; Sabin Kc; Pradip Kandel; Shivish Bhandari; Bishnu Prasad Bhattarai; Hem Bahadur Katuwal; et al. (PLoS ONE)
Understanding the effect of biotic and abiotic factors, including habitat and interspecific competition, is crucial for species conservation. We quantified spatio-temporal patterns of sympatric large Indian civet (LIC; Viverra zibetha) and small Indian civet (SIC; Viverricula indica) using remote cameras in Parsa-Koshi Complex, Nepal during December 2022-March 2023. We found low spatial overlap between LIC and SIC (Oij = 0.15) and high diel overlap between LIC and SIC (Dhat1 = 0.759, normo0 CI: 0.670 ‒ 0.847). Large predators, i.e., tigers (Panthera tigris) and leopards (P. pardus) positively influenced the occurrence of LIC and SIC, respectively. Extent of grassland also positively influenced (0.529 ± 0.193) SIC occurrence. The coexistence of LIC and SIC is governed by complex ecological interactions, including habitat preferences and the influence of predator's occurrences, and such dynamics are important implications for conservation planning. Effective conservation strategies should be considering for the spatial and temporal overlap of these species, considering the role of large predators and habitat variables such as grasslands to support the coexistence of sympatric carnivores and reduce human-wildlife conflict.